Crisis communication strategies of Pertamina during the fuel controversy: A Situational Crisis Communication Theory (SCCT) Perspective - Jerry Rolando; Easter Tobing (Universitas Nusa Cendana, 2026)
Organizational crises can significantly threaten corporate reputation, particularly for companies operating in strategic sectors with high public visibility. Effective crisis communication is essential to manage stakeholder perceptions, reduce uncertainty, and restore organizational credibility. This study examines Pertamina’s crisis communication strategies during the fuel controversy in February 2025 through the lens of Situational Crisis Communication Theory (SCCT). This research employs a qualitative case study approach using directed qualitative content analysis. Data were collected from eight key communication events (CE01–CE08) involving Pertamina, government institutions, technical authorities, and stakeholder representatives during the crisis period. The collected data were analyzed based on SCCT response strategies, including deny, diminish, rebuild, and bolstering strategies, as well as the role of external stakeholder validation in strengthening crisis communication credibility. The findings reveal that Pertamina adopted a multi-strategy crisis communication approach by combining diminish, rebuild, and bolstering strategies throughout different stages of the crisis. During the initial response phase, Pertamina primarily used clarification and technical explanation to reduce stakeholder uncertainty. As reputational risks increased, the organization incorporated accountability and corrective communication through rebuilding strategies. External validation further from independent institutions and government stakeholders contributed to strengthening communication credibility and supporting stakeholder confidence. Theoretically the research extends the application of SCCT beyond organizational response strategies by incorporating the role of external institutional credibility in reputation recovery. Practically, the findings provide guidance for organizations operating in high-risk and public-oriented industries by emphasizing the importance of transparent communication, stakeholder engagement, and adaptive crisis response strategies. Keywords: Crisis Communication; Situational Crisis Communication Theory; SCCT; Reputation Management; Stakeholder Trust; Qualitative Content Analysis; Pertamina